Links Between Remembered Childhood Emotion Socialization and Adult Adjustment: Similarities and Differences Between European American and African American Women - Leerkes, Esther M. (J Fam Issues, 2013)
The purpose of this paper was to examine whether recollections of mothers’ emotion socialization practices during childhood are linked to adult emotional well-being as indexed by depression, trait anger, and cardiac vagal tone, and whether these effects vary for African American and European American women. Participants included 251 women (128 European American; 123 African American) who ranged in age from 18 to 44 years (M = 25 years). Multigroup confirmatory factor analyses indicated strong measurement and factor invariance across African American and European American participants. Remembered non-supportive emotion socialization was linked with elevated depressive symptoms for European American women, but not African American women and with elevated trait anger for both groups. Remembered supportive emotion socialization was linked with higher resting vagal tone for both groups. The results provide some support for the view that non-supportive emotion socialization may be more detrimental for European Americans than African Americans.